Product attributes important to US adult consumers’ use of electronic nicotine delivery systems: a discrete choice experiment - Micah Berman; Erin L Sutfin; Clare Meernik; Gary A Zarkin; Leah M Ranney; Adam O Goldstein; Christine E Kistler; Keith Chrzan; Christopher J Wretman; Chineme Enyioha (BMJ Open)
Objective To understand the importance of electronic nicotine delivery systems (ENDS) product attributes to adult consumers in the USA by age and gender.Design Cross-sectional survey with a discrete choice experiment (best–worst, case 2, scaling) of 19 choice tasks in which participants answered what would make them most want to use and least want to use an ENDS product.Setting and participants A national sample of adults (aged 18+ years) in the USA who had tried an ENDS product at least once.Measures We included 9 ENDS attributes with levels that varied across 19 choice tasks. We performed a multinomial logistic regression to obtain overall importance scores, attribute-level part-worth utilities and most important attribute.Results Of 660 participants, 81% were white, 51% women and 37% had at least a 4-year college degree with an average age of 42.0 years (SD ±19.4). The attributes had the following importance: harms of use 17.6%; general effects 14.1%; cessation aid 12.6%; purchase price 12.1%; monthly cost 12.0%; nicotine content 11.4%; flavour availability 8.4%; device design 7.2%; modifiability 4.6%. Harms of use was the most important attribute for all ages and genders (p<0.05); variation in other important attributes existed by age though not by gender.Conclusion This study identified the importance of nine ENDS attributes. Perceived harms of use of ENDS use appeared most important, and modifiability was least important. Variation by consumer group existed, which may allow for targeted interventions to modify ENDS use.